FACTORS THAT INFLUENCE BRAND SWITCHING BEHAVIOR OF TRI MOBILE CARD USERS AMONG STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, MALIKUSSALEH UNIVERSITY - M. Syariful Alam; Khairina AR; Ikramuddin; M.Subhan (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of price, product quality, consumer satisfaction, and variety seeking tendencies on brand switching decisions. A case study was conducted on 100 Tri card users at the Faculty of Economics and Business, Malikussaleh University. Data were collected through an online questionnaire and analyzed using the Partial Least Square (PLS) method. The results showed that price did not have a significant influence on brand switching decisions. This indicates that consumer perceptions of price, whether considered expensive or competitive, were not a major factor in brand switching decisions. Conversely, product quality was proven to have a positive and significant influence on brand switching decisions. Signal quality, network stability, data package durability, and service features were the dominant factors that encouraged consumers to switch to another brand. Consumer satisfaction did not have a significant influence on brand switching decisions, which means that even though consumers were quite satisfied, this did not guarantee they would remain loyal to using Tri cards. In addition, variety seeking also did not have a significant influence on brand switching decisions. Thus, brand switching decisions among Tri card users were more influenced by product quality aspects than by price, satisfaction, or the tendency to try new products.